The Influence of Canva Application on the English Language Learning Outcomes Students of SMA Muhammadiyah Rappang - Syahrir L; Isumarni Isumarni; Nurul Faradillah; Nur Hikmah (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
The research entitled